Governance, Social Control and Legal Reform in China Community Sanctions and Measures - Chen, Qi (Palgrave Advances in Criminology and Criminal Justice in Asia, 2018)
This book outlines how community sentences and early release options are administered in China. Chen provides empirical insights into the emerging community sector of the Chinese penal system, and illustrates how Chinese criminal courts decide between imprisonment and community sentences. Drawing on interviews with government and non-governmental supervisors, this methodological and rigorous study offers an in-depth discussion of the enforcement of these community sanctions and measures (CSM). By using the CSM reform as an example, this book illustrates the adaptation of Chinese governance and social control. Ultimately, Chen argues that the current model of governance in China (disciplinary governance) cannot guarantee an effective state-agent relationship; it also denies local governments sufficient legitimacy to secure social stability. Finally, proposing that only the rule of law and an active judiciary can complement these two deficiencies, this book will be of great interest to scholars of criminology, law, and penology, as well as anyone who is interested in how China is held together in a socio-legal sense.